DYNAMICS OF PROBLEM OF ALTRUISM LIKE PSYCHOLOGY-PEDAGOGICAL CATEGORY - Stoiko, Kateryna (Educological discourse, 2018)
The article presents the definition of altruism such as philosophical, social and psychological-pedagogical category. In this case, proposed the designation "altruism" is understood like an ethic principle and moral practice of concern for the happiness of other human beings, resulting in a quality of life both material and spiritual. The concept has a long history in philosophical and ethical thought. The term was originally coined in the 19th century by the founding sociologist and philosopher of science, August Comte, and has become a major topic for psychologists (especially evolutionary psychology researchers), evolutionary biologists, and ethnologists. Whilst ideas about altruism from one field can affect the other fields, the different methods and focuses of these fields always lead to different perspectives on altruism. Category altruism was reflected in pedagogical science. The article presents different views on the interpretation and understanding of the problem of altruism and its importance in the educational process. The preconditions of entering the category of altruism in the world and domestic pedagogical thought are considered. The above-mentioned problem has been investigated in the historical aspect. The generalization of the theory of the origin of altruism, the peculiarities of manifestations, factors, inducing to altruistic behavior is carried out. The urgency of consideration of a problem at the present stage of educational work of pupils is considered. The opinions of scientists N.Eisenberg, S.Goncharenko, V.Efroimson, D.Kleery, O.Kont, D.Maers, G.Mironova, A.Moiseeva, M.Snyder about an understanding of a category of altruism are offered. The generalization of the theory of the origin of altruism, the peculiarities of manifestations, factors, inducing to altruistic behavior is carried out. The urgency of consideration of a problem at the present stage of educational work of pupils is considered.